2017
DOI: 10.3329/bjms.v16i3.32849
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of lipid levels of subjects seeking laboratory services in an established laboratory in the Dhaka city

Abstract: Background: Dyslipidemia is linked to the risk for coronary ischemic and cardiovascular disease. Considering the absence of national reference level for lipids in Bangladesh the present study was undertaken to look into the pattern of lipid levels among patients seeking laboratory services in a private medical college hospital.Materials and Methods: This cross sectional study was carried out in Ibn Sina Medical College Hospital in Dhaka city. Patients with antilipid and other medication which might affect the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Postmenopausal women often have increased LDL levels and decreased HDL values. At the current levels, estrogen medication seems to prevent this drop in HDL 11 . Postmenopausal estrogen's effects on heart disease, cancer, and osteoporosis are still being discussed 12,13 .…”
Section: Methodsmentioning
confidence: 86%
“…Postmenopausal women often have increased LDL levels and decreased HDL values. At the current levels, estrogen medication seems to prevent this drop in HDL 11 . Postmenopausal estrogen's effects on heart disease, cancer, and osteoporosis are still being discussed 12,13 .…”
Section: Methodsmentioning
confidence: 86%
“…MS patients had a large myocardial mass, LV diameter, hypertrophy of the interventricular septum, and posterior LV wall. 28 Patients of group I showed more pronounced dilatation of the right ventricle, which can be associated with the development of pulmonary hypertension in obese patients with MS. Pathophysiological changes are associated with the possible development of sleep apnea syndrome, which leads to an increase in pressure in the pulmonary artery, hypertrophy and dilatation of the right ventricle and impairment of its function.…”
Section: Ethical Clearancementioning
confidence: 93%
“…It was also found that 1% rise in serum total cholesterol level leads to 2% increase in ischaemic heart disease (IHD). Regarding Bangladeshi population mean LDL cholesterol level is 119mg/dl 11 . In NICVD a study was done regarding the LDL cholesterol level in ACS patient during 2016 to 2018 period.…”
Section: Introductionmentioning
confidence: 99%